Immaculate Conception Convent in city of La Plata, Bolivia (1540): A look to the colonial area design - Matas Musso, Josefina Leonor (Universidad ORT Uruguay, 2020)
The objective of this article is to characterize one of the convents founded by the Franciscans in Sucre, as a response to the needs and requirements of the place and historical moment, carrying out an architectural analysis from the morphological, functional, spatial and stylistic aspects. To collect the information, an intensive review of primary sources obtained from the National Archive of Sucre was carried out, as well as a review of secondary sources, highlighting the work of researchers José de Mesa and Teresa Gisbert, together with rigorous field work aimed at Survey of the convent and the wooden architecture, in order to identify the furniture of the complex, a subject that has been scarcely or not registered to date. To fulfill the objective of this work, the history of the construction is presented, as well as the description and analysis of the convent and the temple, taking into account the influence of the altarpieces, in order to understand the relationship between the components to finish with the analysis of the exterior architecture.